Neutrophil-to-Lymphocyte Ratio Is a Useful Marker for Predicting Histological Types of Early Gastric Cancer - Yasui, Sho (J Clin Med, 2021)
Background: The indications for endoscopic submucosal dissection (ESD) for gastric cancer are based on preoperative histological assessment; however, examination of tissue biopsy is not always reliable as only a limited portion of the lesion can be obtained. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are markers of inflammatory response and are potentially associated with the grade of malignancy in gastric cancer. We aimed to investigate the association between NLR and PLR and the histology of gastric cancer. Methods: This study included 218 patients who underwent ESD for gastric cancer. The relationship between NLR/PLR and histological diagnosis was investigated. Results: Patients with adenocarcinomas showed significantly higher NLR and PLR than those with adenomas (p < 0.001 and p < 0.05, respectively). Further, patients with undifferentiated adenocarcinoma showed a significantly higher NLR (p < 0.05) than those with differentiated adenocarcinoma. Conclusion: This study suggests that NLR could be a useful marker for assessing early gastric cancer.